Role of Lifestyle in Anorectal Disorders. - Kumar, Suresh; Sharma, Manish Kumar; Sharma, Manish Kumar; Choudhary, Amit; Dhankar, Sanjay (International Research Journal of Ayurveda & Yoga, 2023)
Introduction-Ayurveda is wisdom of life that aims at maintaining normal health of an individual along with treatment of colorful diseases. Applicable Aahara( salutary habits) and House( life) plays a vital part in maintaining normal health and also in treatment of colorful diseases along with the use of drug. In moment’s period with rapid-fire profitable development there’s an increase in irregular and unhappy salutary habits and life, which are major reason for increase in a sedentary life and disturbed digestion( due to MandAgni) leading to circumstance of Gudagata Rogas ( anorectal diseases) like Bhagandara( Fistula- in- ano), Arsha ( haemorrhoids), Parikartika ( chink- in- ano), Guda Kandu( pruritis ani) etc. There diseases recur after eventually indeed after surgical intervention due to unhappy Aahara( salutary habits) and Vihara( diurnal routine) of cases, so it’s veritably important to educate cases regarding Aahara and Vihara. Material & Methods-Material has been collected from Ayurvedic Samhitas, different Research Articles, the internet, etc. Discussion- In this composition a trouble is made to punctuate a chastened protocol in view of ancient Acharyas regarding applicable Aahara and House for a complaint-free society.